A Simple Kinetic Monte Carlo Approach for Epitaxial Submonolayer Growth (Communications in Computational Physics, 2008)
Two-component submonolayer growth on triangular lattice is qualitativelystudied by kinetic Monte Carlo techniques. The hopping barrier governing surfacediffusion of the atoms is estimated using pair interaction potentials. Several degreesof freedoms enhancing the surface diffusion of atoms are also introduced. The mainadvantages of the presented technique are the reduced number of free parameters andthe clear diffusion activated mechanism for the segregation of different types of atoms.The potential of this method is exemplified by reproducing (i) phase-boundary creation and dynamics related to vacancies and stacking faults; (ii) a special co-depositionand segregation process where the segregated atoms of the second component surround the islands formed by the first type of atoms.